Comparative validation of the IPAQ and the 7-Day PAR among women diagnosed with breast cancer - Rock Cheryl L; Gilpin Elizabeth A; Sallis James F; Johnson-Kozlow Marilyn; Pierce John P (BMC, 2006)
Abstract Background The criterion-related validity and measurement bias of the long form of the International Physical Activity Questionnaire (IPAQ) was compared to the 7-Day Physical Activity Recall (PAR). Methods Participants were women who have been diagnosed with breast cancer and enrolled in the ongoing Women's Healthy Eating and Living Study. Women (N = 159, average age 57 years) wore an accelerometer for one week and then completed the IPAQ or the PAR. Results The validity correlation of the PAR was significantly higher (p < 0.001) than the IPAQ (0.73 vs. 0.33, respectively). The PAR and IPAQ overestimated total physical activity by 13% vs. 247%, respectively. The PAR had better sensitivity (p = 0.14) and specificity (p < .01) than the IPAQ (100% vs. 71% and 84% vs. 59%, respectively) in predicting attainment of the ACSM physical activity guideline. Conclusion The PAR was superior to the IPAQ in terms of validity, measurement bias, and screening statistics.